Xtreme illusions 2 - Sarcone, Gianni A; Waeber, Marie - Jo (Washington National Geographic, 2015)
Watch out! This book will scramble your eyeballs and boggle your brain with Perplexing Puzzles, Impossible Illusions, Loopy Lines, and more dizzying delights! Sound like fun? Explore the mysteries that lie right inside our own minds (including the key scientific concepts of perspective and perception) and share the magic with your friends and family
Arts (Games & Recreations)
Keywords: Games